American Struggle for Global Leadership and the Strategic Options for Serbia - Lišanin, Mladen (Serbian political thought, 2023)
Contemporary turbulence regarding the issue of global leadership (referred to by some authors as “primacy” or “hegemony”) takes place within a specific context, manifested through a single fundamental rift: the one based on key actors’ attitudes towards the necessity of structural revision of the world system, contrasted with aspirations to maintain the status quo. In other words, the struggle for global leadership not only has different goals, but also a different logic altogether, if it is observed from the aspect of a declining hegemon, or from the aspects of its challengers. At the same time, the fact that the hegemon is usually a status quo power, seeking to maintain the basic global parameters of power distribution, does not mean that it will not behave in a revisionist manner in various subsystem (regional and sub-regional) frameworks. One of the sub-regions in which the inverse logic of the actions of the global hegemon and those of its challengers on the status quo – revisionism spectrum is apparent, is the Western Balkans. Such behavior, as well as the conditions of increased complexity of foreign policy determinants from the system and regional levels, have consistently incentivized Serbia to opt for the strategy of hedging, in order to compensate the costs incurred in some areas by gains in others. The field of defence and security in the form of joint exercises and arms procurement, has been of particular importance in this regard, as Serbia has been pursuing close and dynamic relations with a wide range of partners, including the US, Russia, China, Israel, France and other European countries, NATO members and non-members alike.  In terms of Serbian-American relations, NATO remains a crucial catalyst; however, the US is increasingly engaged in a more straightforward, bilateral manner – e.g. with regard to the Kosovo and Metohija issue, which is yet another motive for Serbia to maintain its hedging strategy. The trends of global primacy competition, dramatically accelerated at the beginning of the third decade of the 21st century, particularly as the war in Ukraine keeps unfolding, will remain a determinant which strategic options of Serbia largely depend upon. Hedging is most likely to remain the key feature of Serbia’s strategic posture, although there is a possibility this might change in light of a potentially renewed transatlantic and intra-European political coherence.
Keywords: United States of America, Serbia, international relations, hegemony, foreign policy strategy, balancing, hedging, realism